PENGARUH PSIKOEDUKASI KELUARGA TERHADAP KEMAMPUAN KELUARGA DALAM MERAWAT PENDERITA SKIZOFRENIA - Tri Nuhudi Sasono; Faizatur Rohmi (The Indonesian Journal of Health Science, 2017)
The presence of stigma and discrimination against with mental disorders encourage some parties either form government or non goverment organization develops several methods to improve healing in people with mental disorders. The act of them is mentoring the family with mental disorders. The nursing intervension that can be given to the family is psychoeducation. The purpose of this study is to detemine the influence of family psychoeducation on the ability of families in caring for schizophrenia patients. The kind of research used is that of quasi-experiment by pre- and post-test controll group design. Data were collected of research subjects consisted of 24 divided into control group and treatment group. Psychoeducation performed for 5 weeks with a frequency of 5 times with the duration of each time 45-60 minutes. Based on test results with Mann Whitney obtained p value 0.05 which means that comparison between the control group and treatment group showed significant improvement ability. The conclusion in this study is that psychoeducation has been proven to be effective in improving ability of family in treating people with schizophrenia. The nursing implications in this study are expected that psychoeducation becomes one part of promotive health efforts Keywords: Psikoedukasi, family, skizofrenia